NILAI-NILAI MODERASI BERAGAMA DI PONDOK PESANTREN SHOHIFATUSSHOFA NW RAWAMANGUN - Masturaini Masturaini; Yunus Yunus (Universitas Muhammadiyah Tangerang, 2022)
Islamic boarding schools are the front line in anticipating a change. Because Islamic boarding schools are considered a source of moral and moral education both in terms of individuals and groups. History records that pesantren are not only able to survive in the face of the challenges of the times, but also experience rapid development and transformation from time to time. This research is a qualitative research that uses a phenomenological approach. Sources of data, namely primary data sourced from kiai, coaches, teachers, students. Meanwhile, secondary data were taken from documents related to the research. The instrument used in collecting data is the researcher himself whose function is to determine and select informants as data sources, analyze data, interpret data, and the instruments in collecting data are observation, interviews, and documentation. The results of the research on the work of the Shohifatusshofa Islamic Boarding School Nahdatul Wathan have brought a positive impact on plural society in South Sukamaju District. In the model of education and the development of Islamic moderation teachings in various circles and classes of society. The values are as follows; a) Tawassut (middle way); b) Tawazun; c) I'tidal; d) Tasamuh; e) Musawah; f) Shura (consultation); g) Islah; h) Tathawwur wa ibtikar; i) Tahaddur; j) Wataniyah wa muwatanah; k) Qudwatiyah. 3) Instilling the values of Islamic moderation in the Shohifatusshofa Islamic Boarding School by applying several methods, namely; first, the madrasy/formal class method, in the form of classroom education that follows the national education system with subjects arranged based on the national curriculum. Second, the halaqah method. Halaqah recitations are delivered by the kiai at the end of every sunset and dawn at the mosque by studying the yellow book. Third, the hidden curriculum is everything that affects students related to positive behavior